2019
DOI: 10.3390/jmmp3030063
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Tool Wear and Hole Quality during Low-Frequency Vibration-Assisted Drilling of CFRP/Ti6Al4V Stack

Abstract: The use of lightweight material such as CFRP/Ti6Al4V in stacked structures in the aerospace industry is associated with improved physical and mechanical characteristics. The drilling process of nonuniform structures plays a significant role prior to the assembly operation. However, this drilling process is typically associated with unacceptable CFRP delamination, hole accuracy, and high tool wear. These machining difficulties are attributed to high thermal load and poor chip evacuation mechanism. Low-frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 45 publications
1
16
0
2
Order By: Relevance
“…Compared to the CD at N= 2000 rpm, the analysis of the results showed that the cutting tool temperature under LF-VAD was reduced by 40 % for dry coolant condition [11], and 65 % for MQL coolant condition, respectively, as shown in Figure 4. For high cutting speed (N= 3000 rpm), tool-chip welding has been con rmed as the main issue that resulted in stopping the drilling process at the second hole for CD, and hole number 20 for LF-VAD with A m = 0.25 mm, as reported in [11]. The use of MQL resulted in a successful machining process of 50 drilled holes without any observation of the tool-chip welding process.…”
Section: Cutting Temperaturementioning
confidence: 97%
See 4 more Smart Citations
“…Compared to the CD at N= 2000 rpm, the analysis of the results showed that the cutting tool temperature under LF-VAD was reduced by 40 % for dry coolant condition [11], and 65 % for MQL coolant condition, respectively, as shown in Figure 4. For high cutting speed (N= 3000 rpm), tool-chip welding has been con rmed as the main issue that resulted in stopping the drilling process at the second hole for CD, and hole number 20 for LF-VAD with A m = 0.25 mm, as reported in [11]. The use of MQL resulted in a successful machining process of 50 drilled holes without any observation of the tool-chip welding process.…”
Section: Cutting Temperaturementioning
confidence: 97%
“…Abrasive wear of the hard carbon ber particles [8][9][10][11], and adhesion wear mechanism during the drilling process of Ti6Al4V. The machining process of Ti6Al4V resulted in a signi cant increases on the cutting tool temperature due to the low thermal conductivity, and the continuous chip morphology of Ti6Al4V [11,12]. The high cutting temperature has a severe effect on the cutting tool condition, particularly during the drilling process where the poor evacuation mechanism located.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations